A importância da realização de ações culturais e educativas em arquivos - ARAUJO, Neide Rodrigues de (2016)
The present paper approaches the importance of the realization of cultural and educative actions in archives. Thus, it demonstrates a possibility of thinking the archive as a tool of cultural and educative action, going beyond its primordial function, which is the collection, preservation and organization of document founds. The main objective is to verify if there are cultural and educative actions in the Archive of the Casa de José Américo Foundation. It is characterized as an explicative research with qualitative approach. Also, the questionnaire was used as research toolin the data collection. The questionnaire was composed by five variables of subjective character, which was applied with the archive director. From the collected information, it is possible to conclude that the main activities related to cultural and educative actions are technical visits, seminars, courses and lectures.